Assessment of platelet-to-white blood cell ratio on short-term mortality events in patients hospitalized with acute decompensated heart failure: evidence from a cohort study from Jiangxi, China - Xin Huang; Xin Huang; Xin Huang; Xin Huang; Maobin Kuang; Maobin Kuang; Maobin Kuang; Maobin Kuang; Jiajun Qiu; Jiajun Qiu; Jiajun Qiu; Jiajun Qiu; et al. (Frontiers in Cardiovascular Medicine)
ObjectivePlatelet-to-white blood cell ratio (PWR) as a comprehensive indicator of inflammatory response has been widely used to assess the prognosis of various diseases. However, the relationship between PWR and adverse outcomes in patients with acute decompensated heart failure (ADHF) remains unclear. This study aimed to evaluate the association between PWR and all-cause mortality within 30 days of hospitalization in ADHF patients from Jiangxi, China.MethodsA total of 1,453 ADHF patients from the Jiangxi-ADHF study1 cohort were included. The primary outcome measure was all-cause mortality within 30 days of hospitalization. Multivariable Cox proportional hazards regression, restricted cubic spline regression, and receiver operating characteristic curve analysis were employed to explore the association between the inflammatory marker PWR and all-cause mortality in ADHF patients within 30 days of hospitalization.ResultsDuring the 30-day observation period, a total of 53 subjects experienced mortality events. Multivariable Cox regression showed a negative correlation between PWR and all-cause mortality within 30 days of hospitalization in ADHF patients. Restricted cubic spline regression demonstrated an L-shaped association between PWR and 30-day mortality risk (p for nonlinear = 0.038). Further threshold analysis revealed a threshold point for PWR at 15.88, where a decrease in PWR below this threshold was significantly associated with increased risk of all-cause mortality (p for log-likelihood ratio test = 0.046). Additionally, the results of receiver operating characteristic curve analysis indicated that PWR had high predictive accuracy for mortality events within 30 days of hospitalization in ADHF patients and is significantly better than the traditional HF marker N-Terminal Pro-Brain Natriuretic Peptide (AUC: NT-proBNP 0.69, PWR 0.76; Delong test P < 0.05). Subgroup analysis showed that compared to subjects with reduced or moderately reduced ejection fraction, ADHF patients with preserved ejection fraction had a lower risk of short-term mortality associated with PWR (HR:0.99 vs. 0.98 vs. 0.87, P for interaction = 0.0067).ConclusionThis study reveals, for the first time, a negative correlation between the inflammatory marker PWR and all-cause mortality within 30 days of hospitalization in ADHF patients. Based on the threshold analysis findings, patients with ADHF and a PWR below 15.88 had a significantly higher risk of death within 30 days.